105 Finding the culprit of the culprit lesion: the relationship between maximum necrotic core site and minimum lumen area using virtual histology. (22nd September 2015) - Murray, S W; Stables, R H; Hart, G; Perry, R A; Palmer, N D
Abstract : Introduction: In current practice angiographic assessment of the culprit lesion is the main approach to planning the percutaneous revascularisation strategy in high-risk acute coronary syndromes (ACS) patients. Previous histopathology studies in ACS patients have highlighted the presence of multiple vulnerable plaques along the length of the proximal coronary tree. Furthermore, it is suggested that the most vulnerable part of a culprit lesion does not occur at the most stenotic point, as it may lie in adjacent remodelled disease, not visualised by conventional angiography. We determined the relationship of the most vulnerable region to the minimum lumen area using intravascular ultrasound derived virtual histology (IVUS-VH) and compared this to areas of non-culprit disease. Methods: This was a single centre, prospective, observational study that had received local ethical approval. The CL was predetermined by two operators based upon ECG changes and angiographic appearance. Successful IVUS-VH imaging of the entire culprit lesion (CL) (n=15) and non-culprit disease (NCD) (n=15) was undertaken using a phased array catheter (EagleEye catheter, 2.9 F/20 MHz; Volcano Corp) with a continuous motorised pullback of 0.5 mm/s. The plaque composition and analysis was determined by off-line analysis (PC VIAS 3.0.394 software; Volcano Corporation). Plaque constituents were measured over the entire length of a lesion and each individual frame of IVUS-VH was analysed to find the position of both the Minimum Lumen Area (MLA) and the distance to the site of maximum necrotic core % (MAX NC). Necrotic core is the IVUS-VH interpretation of high risk histological tissue that is soft, has no real structure and contains dead cells. Results: A total of 30 lesions and 1774 IVUS-VH frames were included in the analysis. The mean length of the segment analysed in millimetres (mm) did not differ between the two groups (CL=30.5±11.7 vs NCD=25.6±11.9 p=0.18) all of the MAX NC sites lay proximal to the lesion MLA. In the CL the following percentages of MAX NC frames were within the following distances from the MLA: 0–5 mm (26.7%) 5–10 mm (26.7%) 10 mm+(46.7%). The mean distance at which the MAX NC site lay proximal to the MLA site in the CL was 10.4±8.9 mm (95% CI 5.5 to 15.3). For NCD this distance was statistically less at 4.6±2.9 (95% CI 3 to 6.3) p=0.03. MAX NC frames were positioned at the following distances: 0–5 mm (53.3%) 5–10 mm (46.7%). Conclusions: Angiographic assessment alone cannot define the full extent of the culprit lesion. Generally, the most vulnerable areas of plaque are remotely positioned from the most stenotic region. In some cases 46.7% are over 10 mm proximal. Inadequate lesion coverage due to inappropriate stent length selection and placement in the culprit lesion ('longitudinal geographic miss') may be one explanation for the significant recurrent event rate in high-risk ACS patients.